Analisis Komparatif Pengaruh Gaya Hidup terhadap Keputusan Pembelian Produk Fashion Merek Asli dan Tiruan - Dienni Ruhjatini; Bambang Irawan; M Dimyati (RELASI : JURNAL EKONOMI, 2014)
This study compared the use of consumer goods brand fashion genuine and fake brands, therefore, taken 2 segments of the population that is considered to represent the consumers of these two kinds of fashion items. Representingpopulation is Ciputra World Mall visitor segments to represent the middle to upper economic level with the consideration that the Mall visitors are referred to as the group that is identical to a high lifestyle. Meanwhile, to represent a segment of middle and lower economic level, this study chose ITC Mall visitorpopulation. The data used are primary data taken from questionnaires by 240 respondents with 120 respondents to the proportion of each segment. Sampling with accidental sampling technique. With the method of analysis used multiple linear regression analysis with confirmatory approach, the results obtained indicate that the 3 variables: interest, value and demograph has a great influence on purchasing decisions original brand fashion products, while for the consumer lower economic level buying decision got a great influence of the variable activities , Interest and demograph .